The Acquisition of Indirect Speech made by English Foreign Learners, Learning English as a Foreign Language - Solihah, Mar'atus; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph.D (2016)
This present study deals with the acquisition of indirect speech made by English foreign learners, especially junior and senior high school students . The objectives of this research are to identify the pattern of indirect speech from statement, command, and interrogative made by junior and senior high school students The type of this research is qualitative research and cross-sectional study. This study was conducted in MTs N Salatiga and SMA N 3 Salatiga. The data was direct speech which was changed into indirect speech made by junior and senior high school students. In collecting data, the researcher used written sentences of indirect speech made by junior and senior high school students and classified the data based on the dominant pattern found. The researcher used the framework of Goodell&Sachs (1992) and Sridhar (1980) in analyzing the developmental pattern of indirect speech made by the students. The result showed that the eight grade students were still at stage two (Indirect Quote using Present tense) and stage 3: Indirect Quote using Corresponding Past Tense (no change in pronoun and adverb of time) in constructing indirect speech of statement, stage three (: Indirect Imperative using Original Pronoun &Adverb of Time) in command, and stage two (Direct Quote of Interrogative Pattern) in interrogative. Then, tenth grade students were at stage 4 (Indirect Quote using Corresponding Past tense (Correct Change in Pronoun) in constructing statement, stage four (Indirect Imperative Complete) in command, and stage three (Indirect Quote using Original Pronoun/Adverb of Time) in interrogative. Next, eleventh grade students were at stage 4 (Indirect Quote using Corresponding Past tense (Correct Change in Pronoun) in constructing statement, stage four (Indirect Imperative Complete) in command, and stage four (Indirect Quote using Indirect Pronoun/Adverb of Time) in interrogative.